Gene silencing in adult Popillia japonica through feeding of double‐stranded RNA (dsRNA) complexed with branched amphiphilic peptide capsules (BAPCs) - Carroll, Elijah; Kunte, Nitish; McGraw, Erin; Gautam, Sujan; Range, Ryan; Noveron-Nunez, Jose A.; Held, David W.; Avila, L. Adriana (Frontiers in Insect Science, 2023)
Gene silencing by feeding double-stranded (dsRNA) holds promise as a novel pest management strategy. Nonetheless, degradation of dsRNA in the environment and within the insect gut, as well as inefficient systemic delivery are major limitations to applying this strategy. Branched amphiphilic peptide capsules (BAPCs) complexed with dsRNA have been used to successfully target genes outside and inside the gut epithelium upon ingestion. This suggests that BAPCs can protect dsRNA from degradation in the gut environment and successfully shuttle it across gut epithelium. In this study, our objectives were to 1) Determine whether feeding on BAPC-dsRNA complexes targeting a putative peritrophin gene of P. japonica would result in the suppression of gut peritrophin synthesis, and 2) gain insight into the cellular uptake mechanisms and transport of BAPC-dsRNA complexes across the larval midgut of P. japonica. Our results suggest that BAPC-dsRNA complexes are readily taken up by the midgut epithelium, and treatment of the tissue with endocytosis inhibitors effectively suppresses intracellular transport. Further, assessment of gene expression in BAPC- peritrophin dsRNA fed beetles demonstrated significant downregulation in mRNA levels relative to control and/or dsRNA alone. Our results demonstrated that BAPCs increase the efficacy of gene knockdown relative to dsRNA alone in P. japonica adults. To our knowledge, this is the first report on nanoparticle-mediated dsRNA delivery through feeding in P. japonica.